Prognostic impact of progression to induction chemotherapy and prior paclitaxel therapy in patients with germ cell tumors receiving salvage high-dose chemotherapy in the last 10 years: a study of the European Society for Blood and Marrow Transplantation Solid Tumors Working Party - Necchi, Andrea; Wuchter, Patrick; Dreger, Peter (Bone marrow transplantation, 2016)
Little is known about the prognostic impact of prior paclitaxel therapy and response to induction chemotherapy defined as the regimen preceding high-dose chemotherapy (HDCT) for the salvage therapy of advanced germ cell tumors. Twenty European Society for Blood and Marrow Transplantation centers contributed data on patients treated between 2002 and 2012. Paclitaxel used in either prior lines of therapy or in induction-mobilization regimens was considered. Multivariable Cox analyses of prespecified factors were undertaken on PFS and overall survival (OS). As of October 2013, data for 324 patients had been contributed to this study. One hundred and ninety-two patients (59.3%) had received paclitaxel. Sixty-one patients (19%) had a progression to induction chemotherapy, 234 (72%) a response (29 (9%) missing or granulocyte colony-stimulating factor without chemotherapy). Both progression to induction chemotherapy and prior paclitaxel were significantly associated with shorter OS univariably (P<0.001 and P=0.032). On multivariable analysis from the model with fully available data (N=216) progression to induction was significantly prognostic for PFS and OS (P=0.003), but prior paclitaxel was not (P=0.674 and P=0.739). These results were confirmed after multiple imputation of missing data. Progression to induction chemotherapy could be demonstrated as an independent prognostic factor, in contrast to prior paclitaxel.
published online 7 December 2015
Gesehen am 12.03.2020